INTERVENSI YUDISIAL DALAM ISU HUBUNGAN PUSAT–DAERAH: STUDI TERHADAP PRAKTIK MAHKAMAH KONSTITUSI - Kurnia, Titon Slamet (Faculty of Law, Parahyangan Catholic University, 2021)
The legal issue to be discussed in this article is the involvement of the Constitutional Court in adjudicating issues concerning the relationship between national – local government in general, and the distribution of power to the local government in particular. To be more specific, this article will criticise by delivering a casenote over the Constitutional Court decisions, i.e. Decision Number 87/PUU-XIII/2015, Decision Number 137/PUU-XIII/2015, Decision Number 30/PUU-XIV/2016 and Decision Number 56/PUU-XIV/2016. The casenote will notify the need to a deeper conceptual understanding of the differences between unitary State and federalism principles and its implication in giving prescriptions. This is a response to the Constitutional Court’s judicial opinion which tends weightier to federalism, instead of unitary State principle. According to this situation, it is recommended that the Constitutional Court should not review the constitutionality of laws which contain the legal issues concerning the relationship between national – local government in general, and the distribution of power to the local government in particular. This article uses conceptual and comparative approaches.